Evaluation of the prothrombin time for measuring rivaroxaban plasma concentrations using calibrators and controls. Issue 2 (12th March 2012) - Samama, M.; Contant, G.; Spiro, T.E.; Perzborn, E.; Le Flem, L.; Guinet, C.; Gourmelin, Y.; Martinoli, J.L.
Abstract : Background: Rivaroxaban is widely used in clinical practice. Although routine coagulation monitoring is not required, quantitative determination of rivaroxaban might be valuable in certain clinical circumstances. Variation in response sensitivity of prothrombin time (PT) reagents to rivaroxaban is well described in the literature, and the conventional international normalised ratio cannot be used for rivaroxaban. Purpose: This multicentre study assessed the intra and interlaboratory precision of measurements of rivaroxaban plasma concentrations using the PT assay together with rivaroxaban calibrators and controls. Materials and methods: Participating laboratories (Europe and North America) were provided with rivaroxaban calibrators (0, 41, 219 and 430 ng/ml), rivaroxaban pooled human plasma controls (19, 160 and 643 ng/ml) and PT reagent. Evaluation was performed over 10 consecutive days by each laboratory using local PT reagents as well as the centrally provided PT reagent (STA Neoplastine CI Plus; Diagnostica Stago). A calibration curve was produced each day, and day-to-day precision was evaluated by testing three control plasma samples. The control was diluted and re-tested if the level was above the highest concentration of the calibration curve. Results: Intralaboratory variations in PT were dependent on the sensitivity of the local PT reagents, regardless of the type of instrument used. A large inter-laboratory variation (in seconds) was observed with local PT reagents; the coefficient of variation (CV) was 13.6–29.7%. When the results were expressed as rivaroxaban concentration (ng/ml), the inter-reagent variations were reduced; less variation was found with both local reagents (CV: 5.1–15.5%) and the central reagent (CV: 2.2–7.5%). However, over-estimation was observed with both local and central reagents. The CV for the calibrator containing 41 ng/ml rivaroxaban was 5.8% when the central reagent was used. Conclusions: The PT assay may be useful for measuring rivaroxaban peak plasma concentrations (2–3 h after drug intake) using rivaroxaban calibrators and controls.